Aplikasi mHEALTH dalam Manajemen Luka Diabetik - Adelia Pradita; Agung Waluyo; Tuti Herawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the use of mHealth in diabetic wound management. The research method uses a literature review approach through content analysis with a search method using an electronic database consisting of ProQuest, PubMed, Science Direct, Scopus, Sage, and SpringerLink with the keywords